GOVERNANCE OF INSTITUTIONAL WASTE MANAGEMENT IN JEMBER REGENCY - Hikmah, Faiqoh Nurul; Dayar, Mohammad Baladdudin (DIA: Jurnal Administrasi Publik, 2024)
Waste management at the Pakusari Final Disposal Site (TPA) in Jember Regency has yet to find a conducive waste management. This study aims to analyze the institutional governance model of waste management in Jember Regency through an institutional perspective framework according to Pavan et.al 2016. Through a case study at Pakusari TPA which is the largest TPA and accommodates the most waste, namely 17 sub-districts out of 31 sub-districts that scattered in Jember Regency but also experiencing various problems such as over capacity, rejection by the surrounding community and the behavior of the surrounding community who are still ignorant of the awareness of the importance of managing waste properly and maintaining the habit of disposing of waste in the river. Using a qualitative approach this research tries to provide an overview of how the institutional design of Pakusari TPA is in exercising its authority in solving waste problems in Jember district.